The Unifying Moral Dyad: Liberals and Conservatives Share the Same Harm-Based Moral Template. (August 2015) - Schein, Chelsea; Gray, Kurt
Do moral disagreements regarding specific issues (e.g., patriotism, chastity) reflect deep cognitive differences (i.e., distinct cognitive mechanisms) between liberals and conservatives? Dyadic morality suggests that the answer is "no." Despite moral diversity, we reveal that moral cognition—in both liberals and conservatives—is rooted in a harm-based template. A dyadic template suggests that harm should be central within moral cognition, an idea tested—and confirmed—through six specific hypotheses. Studies suggest that moral judgment occurs via dyadic comparison, in which counter-normative acts are compared with a prototype of harm. Dyadic comparison explains why harm is the most accessible and important of moral content, why harm organizes—and overlaps with—diverse moral content, and why harm best translates across moral content. Dyadic morality suggests that various moral content (e.g., loyalty, purity) are varieties of perceived harm and that past research has substantially exaggerated moral differences between liberals and conservatives.